جرائم العنف الاسري للزوجة في قانون العقوبات والاحوال الشخصية العراقي دراسة مقارنة - الحديثي, فخري عبد الرزاق; دلول, رسل فيصل (Journal of Legal Sciences, 2019)
The subject (crimes of domestic violence to the wife in penalties and personal circumstances of the Iraqi law) of the important topics which aims to provide criminal and legal protection for the wife as the interest protected by the law when the criminalization of an act perpetrated spousal violence has spread problem of the most serious problems that have had a significant impact the wife, in particular, on the family and society in general, namely, the problem of protecting the wife of domestic violence, which directs it from her husband, and our goal of this study is to develop develop a wife and protection from domestic violence, which sheds it by searching in the media confront this phenomenon, namely violence prisoners and then stand on the causes, and we divided into two sections search preceded by an introduction and a conclusion conclude it contains the findings and recommendations, Valambges first violent crimes in the Iraqi Penal Code, section II of violent crimes in the personal status Law .